ANALISIS USAHA PENGOLAHAN KOPI ROBUSTA DI KECAMATAN GEMBONG KABUPATEN PATI - Riski Anjar Sari; Shofia Nur Awami; Aniya Widiyani (Universitas Wahid Hasyim, 2019)
ABSTRACT Gembong subdistrict is producing coffee area in Pati Regency which is processed into black coffee powder and green coffee powder. This research aims to know the value-added, income and eligibility processing robusta coffee. The basic method of research used descriptive method. Location retrieval methods of research with purposive sampling. Sampling of respondents by the census method, data collection by way of interviews, observation and record-keeping. The data analysis methods are added value, cost, revenue and earnings, and also feasibility analysis BEP and R/C. The results showed there was a difference in the average of ratio value added processing black and green coffe powder they are 43.52% and 48.06%, the average revenues of coffee powder processing black and green respectively is Rp. 360.592/PP one week and Rp. 580.313/PP one week, the average of breakeven black coffee powder and green coffe powder a value of BEP (Production) 10.90 kg and 4.91 kg (the real are 12.48 kg and 6.84 kg), BEP (Price) of Rp. 90.813/kg and Rp. 154.489/kg (the real are Rp. 104,000/kg and Rp. 215,000/kg) and BEP (Acceptance) of Rp. 751.431/PP one week and Rp.379.426/PP one week (the real are Rp. 1.297.920/PP one week and Rp.1.470.600/PP one week), and R/C value of black dan green coffee powder processing are 1.38 and 1.65. Keywords : Value Added, Robusta Coffee, Black Coffee, Green Coffee, Gembong